PERAN DINAS PARIWISATA KABUPATEN BENGKALIS DALAM PENGEMBANGAN WISATA DI SITUS DATUK LAKSAMANA RAJA DI LAUT KABUPATEN BENGKALIS - Ruth Dwitya Hutagalung; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The role of government tourism office is very important in the development of a tourist attraction. The purpose of this research is to know the role of government tourism office  on Bengkalis Regency in developing the site of Datuk Laksamana Raja Di Laut and what are the inhibiting factors and supporting factors in the development of the site so that later it can increase the number of tourist visits. The research uses a qualitative descriptive method, with data collection techniques used are observation, interviews, and documentation. The results of this research are show that as a motivator Bengkalis Regency Government Tourism Office plays a role in providing motivation to the community in the development and preservation of historical sites and involving the community in its management. As a facilitator, the Tourism Office plays a role in facilitating facilities and infrastructure in stages to meet the needs of visiting tourists. Meanwhile, as a dynamist, the Tourism Office collaborates with various parties such as the community, village administrations office and the government in the development of tourism for Datuk Laksamana Raja Di Laut. The historical value and high Malay culture are supporting factors in the development of historical tourism at the Datuk Laksamana Raja Di Laut site. Meanwhile, the inhibiting factors include the lack of awareness of the surrounding community towards Malay historical heritage, inadequate development funds, and access to Tomb I and Tomb II which can only be passed by motorbike.   Keyword : The Role of the Government Tourism Office, Development,Tourism Datuk Laksamana Raja Di Laut Site.